Predictive factors of outcome in poorly differentiated thyroid carcinomas. (March 2018) - de la Fouchardière, Christelle; Decaussin-Petrucci, Myriam; Berthiller, Julien; Descotes, Françoise; Lopez, Jonathan; Lifante, Jean-Christophe; Peix, Jean-Louis; Giraudet, Anne-Laure; Delahaye, Armelle; Masson, Sandrine; Bournaud-Salinas, Claire; Borson Chazot, Françoise
Abstract: Background: The prognosis of poorly differentiated thyroid carcinomas (PDTC) is heterogeneous though generally poor. The objectives of this study were to identify clinical and molecular factors of poor prognosis. Methods: One hundred four consecutive patients treated for a PDTC between 01/01/2000 and 31/12/2010 were included in this study. A pathological review was done for all cases (blinded to clinical data and outcome). Results: All patients underwent thyroidectomy. Adjuvant radioactive-iodine was administered in 95.2% of them. Tumours were pT3 or pT4 in 68.3% of cases and metastatic in 38.5% of patients. Extrathyroidal extension (ETE) was observed in 40% of patients. At the end of the initial treatment, only 37% of patients were considered in remission. Fifty-two patients (50%) became refractory to radioiodine during follow-up. The 5-year overall survival was 72.8% and the 5-year recurrence-free survival (RFS) was 45.3%. Remission after initial treatment was an independent factor of RFS (HR = 0.22; [0.10–0.49]). ETE was the only significant parameter influencing the overall survival in multivariate analysis. TERT promoter mutations at positions −124 (C228T) and −146 (C250T) were present in 38.1% of analysed patients and significantly associated with radioiodine resistance but not with overall survival. Half of TERT promoter mutant tumours harboured also RAS or BRAF mutations. Conclusion: PDTC form a heterogeneous group of patients with usual late-stage diagnosis, low radioactive iodine avidity and frequent metastatic spread. TERT promoter mutations could help to identify patients with high risk of radio-iodine refractoriness. Highlights: A quarter of analysed PDTC harbored TERT promoter mutations which were significantly associated with radioiodine resistance. A quarter of analysed tumours harboured TERT promoter mutations which were significantly associated with radioiodine resistance.